Exploring the transition to agroforestry for smallholder farmers: a feasibility study for the Ashanti region of Ghana - Dumas, Youp; Ubacht, Jolien; van Andel, Ellen; Keledorme, Lily Akorfa (Frontiers in Sustainable Food Systems, 2025)
Smallholder farmers in the Ashanti region of Ghana face challenges due to shifts in climate patterns that have a significant negative impact on their crop yields. We conducted a feasibility study into the transition toward an agroforestry system by integrating trees and shrubs within crop fields. In this research, we adopted a complex systems perspective to analyse the institutional, social, and technical aspects that play a role in such a transition. By conducting in-depth analyses through three rounds of interviews and a Q-sort method with smallholder farmers in the Ashanti region, we mapped the most important challenges in transitioning to an agroforestry system. These pertain to: uncertainties in land tenure agreements, the absence of effective conflict resolution mechanisms, having no knowledge of and tools for maintaining trees, and the lack of financial resources for upfront investments. Based on our findings, we provide recommendations for the design of the transition process toward a comprehensive agroforestry system in Ghana. We recommend improving land tenure security and establishing conflict resolution mechanisms by polycentric coordination in which all stakeholders are involved for this essential institutional redesign process. To enable smallholder farmers to acquire the required skills and tools for tree crops, preferably a pilot plot for real-life demonstration is initiated. Financial resources for the smallholder farmers in the transition period need to be warranted, e.g., via the design of a carbon credit market. We recommend future research to explore the perspective and interests of chiefs/landowners in the Ashanti region who have crucial decision-making power through their land ownership.